Barbiturate end-capped non-fullerene acceptors for organic solar cells: tuning acceptor energetics to suppress geminate recombination losses. Issue 24 (26th January 2018) - Tan, Ching-Hong; Gorman, Jeffrey; Wadsworth, Andrew; Holliday, Sarah; Subramaniyan, Selvam; Jenekhe, Samson A.; Baran, Derya; McCulloch, Iain; Durrant, James R.
Abstract : We report the synthesis of two barbiturate end-capped non-fullerene acceptors and demonstrate their efficient function in high voltage output organic solar cells. Abstract : We report the synthesis of two barbiturate end-capped non-fullerene acceptors and demonstrate their efficient function in high voltage output organic solar cells. The acceptor with the lower LUMO level is shown to exhibit suppressed geminate recombination losses, resulting in enhanced photocurrent generation and higher overall device efficiency.